Assessing the apparent viscosity of decane-water emulsion in underground porous media based on the lattice Boltzmann method - Shao, Lihua; Lin, Ping; Zhu, Jingwei; Zhou, Yiyang; Xie, Chiyu (Frontiers in Earth Science, 2023)
The groundwater system is one of the most important subsurface resources on Earth, which offers many important services to humankind, such as irrigated agriculture, household use, and manufacturing. However, the safety of groundwater resources is seriously threatened by contamination from human activities. The emulsion has been proposed as a potential solution for the removal of contaminants due to its high apparent viscosity. Here we reveal the pore-scale mechanism for the viscosity increase in decane-water emulsions by lattice Boltzmann simulations. We assess the effect of phase saturation, interfacial tension, and contact angle, on the apparent viscosity of decane-water emulsions in porous media. Our results show that the apparent viscosity of the emulsion reaches its maximum value when the decane saturation is around 20%. We also find that this maximum viscosity increases with interfacial tension, and it is larger in decane-wet or water-wet systems than it is in intermedia-wet media.